Analysis of COVID-19 vaccination experience of the Los Pastos, Wounaan, and Misak Misak indigenous peoples from Bogotá, Colombia. - Sandra Vargas-Cruz; Miguel Baquero-Acuña; Camila Bautista; Juan Castro-Caro; Nicol Espejo; Pedro Ruiz Mateus; Irene Parra-García (PLOS Global Public Health, 2025)
The coronavirus disease 2019 (COVID-19) pandemic was recognized as a public health crisis closely linked to socioeconomic and cultural factors. Vaccination is a long-term solution for COVID-19; however, access to vaccines has been hindered by geographic, cultural, and socioeconomic barriers as well as distrust in the health system-particularly among populations that have experienced historical inequities, such as indigenous peoples. This study aimed to analyze the COVID-19 vaccination experiences of the Misak Misak, Wounaan, and Los Pastos indigenous peoples in Bogotá, Colombia. This was a sequential explanatory mixed-methods study, with the quantitative phase followed by the qualitative phase. We conducted emistructured interviews, 9 sharing circles, and 85 household surveys using a triangulation approach. Results showed that the Los Pastos people had the highest vaccination rate (97.3%), followed by the Misak Misak people (85.2%); the Wounaan people had the lowest vaccination rate (38.5%). The main reason for vaccination among the Misak Misak and Wounaan was that it was mandated by their workplaces or educational institutions. For the Los Pastos, the main reason for vaccination was to protect themselves and their environment. The main reasons for not getting vaccinated included distrust of vaccines, although there were no geographic access barriers. This study revealed varying vaccination rates among indigenous populations living in urban areas, possibly associated with factors such as infodemic, previous distrust of Western health services, and preference for ancestral medicine as an alternative for COVID-19 prevention.